Quebec's Anglohpone Communities and the Legacies of the Quebec Act, 1774-2024 - McGaughey, Jane G.V. (2025)
2024 marked the 250th anniversary of the Quebec Act, a landmark piece of legislation shepherded through the Westminster Parliament by then Governor of Quebec Guy Carleton, later known as Lord Dorchester. This paper explores the reactions of Anglophone communities in Quebec to Carleton’s actions in the 1770s and also in the 1980s, when the disappearance of “Dorchester Boulevard” in Montreal caused mixed reactions. Despite having been raised in an Irish Protestant family that benefited from the punitive anti-Catholic Penal Laws of the 18th century, Carleton broke with established British imperial policies of forced assimilation and territorial expulsion. Instead, he promoted a more pluralistic vision for Quebec where French Canadian Catholics enjoyed civil rights unheard of in the rest of the British Empire. However, while Carleton’s actions permanently affected future ideas of what defined “Canada,” they also alienated many members of the Anglophone community in Quebec City and Montreal on the eve of the American Revolution.